2008
DOI: 10.1002/jctb.1922
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization of malto‐oligosaccharide forming α‐amylase from Bacillus subtilis KCC103: properties and application in starch hydrolysis

Abstract: BACKGROUND: A malto-oligosaccharide forming α-amylase from Bacillus subtilis KCC103 immobilized in calcium alginate beads was repeatedly used in batch processes of starch hydrolysis. The degree of starch degradation and operational stability of the immobilized system were optimized by varying the physical characteristics and composition of the beads. The products formed from hydrolysis of various starches by α-amylase immobilized in different supports were analyzed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…But the immobilized enzyme offered the advantage of using the enzyme in repeated batch reactions. Immobilized beads prepared from 3% (w/v) alginate and 4% (w/v) CaCl 2 were suitable for up to 10 repeated uses, losing only 25% of their efficiency (Rajagopalan & Krishnan, 2008). It was observed that a-amylase covalently immobilized onto phthaloyl chloride-containing amino group functionalized glass beads demonstrated more than 98% activity after six runs (Kahraman, Bayramoglu, Kayaman-Apohan, & Gungor, 2007b).…”
Section: Reactor Studies Using Immobilized Beadsmentioning
confidence: 97%
See 2 more Smart Citations
“…But the immobilized enzyme offered the advantage of using the enzyme in repeated batch reactions. Immobilized beads prepared from 3% (w/v) alginate and 4% (w/v) CaCl 2 were suitable for up to 10 repeated uses, losing only 25% of their efficiency (Rajagopalan & Krishnan, 2008). It was observed that a-amylase covalently immobilized onto phthaloyl chloride-containing amino group functionalized glass beads demonstrated more than 98% activity after six runs (Kahraman, Bayramoglu, Kayaman-Apohan, & Gungor, 2007b).…”
Section: Reactor Studies Using Immobilized Beadsmentioning
confidence: 97%
“…The above features would be important in the development of an economically feasible bioreactor for the starch hydrolysis industry thus immobilizing a-amylase would be of great importance. The general methods employed for immobilization are entrapment, microencapsulation, copolymerization, cross linking, physical adsorption, chemical attachment and covalent binding (Hasirci, Aksoy, & Tumturk, 2006;Markweghanke, Lang, & Wagner, 1995;Mozhaev et al, 1989;Rajagopalan & Krishnan, 2008;Reshmi, Sanjay, & Sugunan, 2006). Immobilization by physical adsorption on inorganic materials such as porous silica (Cao, Bornscheuer, & Schmid, 1999) clay (Sanjay & Sugunan, 2005a, 2005b and collagen (Groom, Meising, & White, 1988) has been reported.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…For food‐industry applications, calcium alginate gels have been investigated due to their compatibility in many food matrices for a variety of enzymes, including cheese ripening enzymes, glucose isomerase, and β‐ d ‐galactosidase . That said, there has been limited investigation into the efficacy of alginate as an entrapment matrix for ɑ‐amylase, whose substrate (starch, a polymer of ɑ‐1,4 linked glucose monomers) is substantially larger than the aforementioned enzymes . With proper supplementation of the alginate with silica gel, improved immobilization efficiency, and reusability was observed with the immobilized enzyme compared to without added silica.…”
Section: Other Proposed Strategiesmentioning
confidence: 99%
“…Thus, immobilization is an important tool for the stability and frequent use of enzymes in industrial application and for its rapid separation from the reaction mixture. Immobilization of the enzyme can be achieved in one of the following ways like entrapement, coplymerization, microencapsulation, cross-linking, covalent binding, chemical attachment and physical adsorption (Hasicri, Aksoy, and Tumturk, 2006;Rajagopalan and Krishnan, 2008;Reshmi, Sanjay and Sugnan, 2006). As a result, the above features are important for the development of economically feasible bioreactor.…”
Section: Review Articlementioning
confidence: 99%